2021
DOI: 10.3390/pharmaceutics13122102
|View full text |Cite
|
Sign up to set email alerts
|

Biomedical Applications and Bioavailability of Curcumin—An Updated Overview

Abstract: Curcumin, a yellow-colored molecule derived from the rhizome of Curcuma longa, has been identified as the bioactive compound responsible for numerous pharmacological activities of turmeric, including anticancer, antimicrobial, anti-inflammatory, antioxidant, antidiabetic, etc. Nevertheless, the clinical application of curcumin is inadequate due to its low solubility, poor absorption, rapid metabolism and elimination. Advancements in recent research have shown several components and techniques to increase the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
80
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(80 citation statements)
references
References 233 publications
0
80
0
Order By: Relevance
“…The major pharmacologically active constituents of Curcuma species are curcuminoids and essential oils. Curcuminoids, a mixture of three phenolic compounds namely curcumin, demethoxycurcumin, and bis-demethoxycurcumin, have been proven to posses significant health benefits along with the potential to prevent various diseases [ 4 , 5 , 6 ]. Essential oils of Curcuma species are relatively complex with hundreds of components including terpenes and oxygenated terpenoids.…”
Section: Introductionmentioning
confidence: 99%
“…The major pharmacologically active constituents of Curcuma species are curcuminoids and essential oils. Curcuminoids, a mixture of three phenolic compounds namely curcumin, demethoxycurcumin, and bis-demethoxycurcumin, have been proven to posses significant health benefits along with the potential to prevent various diseases [ 4 , 5 , 6 ]. Essential oils of Curcuma species are relatively complex with hundreds of components including terpenes and oxygenated terpenoids.…”
Section: Introductionmentioning
confidence: 99%
“…Curcumin (diferuloylmethane) is a natural polyphenolic substance derived from the plant Curcuma longa . It has demonstrated various biological properties, such as antioxidant, antibacterial, antifungal, antiviral, anti-inflammatory, anticancer, antiproliferative, proapoptotic and anti-atherosclerotic effects, leading to medicinal benefits against various forms of human illnesses [ 43 , 44 ]. However, Curc is characterized with low aqueous solubility, photodegradability, chemical instability, rapid metabolism and elimination that hamper its clinical application.…”
Section: Resultsmentioning
confidence: 99%
“…There have been multiple reviews and research articles reported in the literature to increase the bioavailability of curcuminoids using various formulations [ 1 , 24 , 25 , 26 , 27 , 28 ]. Maheshwari, in 2010, reported higher solubility of lipophilic curcuminoids in traditional vehicles such as milk, clarified butter, and corn oil, as shown in the current study.…”
Section: Resultsmentioning
confidence: 99%